Eksplorasi Makna Tradisi Bersih Desa terhadap Perilaku Sosial Masyarakat di Desa Wedoro Kabupaten Sidoarjo - Indana Zulfa; Ananda Aulia Rahma; Fariha Zahro Hasanah; Listyaningsih Listyaningsih (Yayasan Literasi Sains Indonesia, 2026)
One of the Javanese traditions that still survives today is the village cleaning tradition, which is maintained and preserved by the residents of Wedoro Village, Sidoarjo Regency, amid the rapid pace of modernization. This study aims to analyze the meaning of the village cleaning tradition in relation to the social behavior of the community and to identify preservation strategies that have been implemented to ensure that it remains relevant in this day and age. The research uses a descriptive qualitative method involving eight informants consisting of community leaders, teenagers, and residents of Wedoro Village, Sidoarjo Regency as subjects, while data is obtained through interviews, observation, and documentation. The results of the study show that the meaning of the village cleaning tradition is not just an annual ritual, but also contains religious and social values, such as expressions of gratitude, prayers for safety, respect for ancestors, and strengthening solidarity and mutual cooperation. Preservation strategies are carried out through the active participation of the younger generation, adaptation to community culture, creative innovations that do not eliminate the core values of tradition, embracing residents through existing institutions, and encouragement from parents. These findings are linked to Talcott Parsons' AGIL theory, which emphasizes adaptation to the tide of modernization, the achievement of goals in the form of togetherness and prosperity, integration through the strengthening of social solidarity, and the maintenance of patterns by preserving and passing on cultural values as a whole.